A comparative prospective study of laparoscopic guided needle assisted hernial sac ligation versus open herniotomy surgery in congenital inguinal hernia management - Prasad, Dinesh; Satani, Yogesh; Bochiya, Girish (International Surgery Journal, 2021)
Background: To evaluate if significant difference exists in surgical outcome following laparoscopic guided needle assisted congenital hernial sac ligation versus conventional open Herniotomy as later is treatment of congenital hernia and laparoscopy guided emerged as newer alternative. Objective was to know whether a significant difference exists in surgical outcomes following laparoscopic guided needle assisted congenital hernial sac ligation and conventional herniotomy in terms of mean operative time, post operative pain, recurrence, local complication, cosmetic results. Methods: Patients were randomized on basis of odd and even registrations for surgery in our institute. Patients who undergone laparoscopic guided needle assisted congenital hernial sac ligation or who undergone conventional open herniotomy for congenital hernia between November 2018 to April 2020 (50 in each arm) were followed for 1, 3, 6 and 12 months to evaluate the outcomes. Results: In our study, major complication in open herniotomy group was surgical site infection (22%), hematoma (10%), intra operative bleeding (16%), seroma formation (8%) with minimum operative duration was ~60 minutes, hospital stay of 2-3 days while no such complication reported in laparoscopic guided needle assisted hernia sac ligation group being operative time of ~20 minutes, hospital stay of 1 day with better cosmetic results. Conclusions: We conclude that laparoscopic guided needle assisted hernial sac ligation is simple, safe, efficacious with its own advantage in comparison to conventional open herniotomy and should be acceptable alternative to traditional open herniotomy approach for congenital hernia.